Prevalence of cardiac amyloidosis in patients with unexplained left ventricle hypertrophy. (14th October 2021) - Holcman, K; Kostkiewicz, M; Szot, W; Lesniak-Sobelga, A; Hlawaty, M; Wisniowska-Smialek, S; Dziewiecka, E; Karabinowska, A; Stepien, A; Graczyk, K; Mroz, K; Podolec, P; et al.
Abstract: Background: Amyloid cardiomyopathy (CA) it is more frequently diagnosed due to rapidly developing imaging modalities. Misfolding of transthyretin (TTR) is the source of two distinct forms of amyloidosis (ATTR): acquired wild-type (ATTRwt) and hereditary (ATTRm). Types of TTR gene variants display genetic and ethnic variability. The aim of this prospective study was to assess the prevalence and types of pathogenic genetic variants associated with ATTRm amyloidosis in patients with unexplained left ventricle (LV) hypertrophy. Methods: We evaluated prospectively 101 consecutive patients (37 (37%) females, age: 69.7±13.6 y.o.) in years 2016–2021. Analysis included clinical data, free light chain blood immunoglobulins and urine immunofixation, transthoracic echocardiography (TTE), single-photon emission computed tomography (SPECT) with 3, 3-disphono-1, 2-propanodicarboxylic acid (DPD), and in selected cases cardiac or soft tissue biopsy. Patients with DPD cardiac uptake in SPECT or positive histopathology or family history of ATTR were subjected to genetic testing by an amplicon-based next-generation TTR sequencing approach. Results: Enrolled patients presented with marked LV hypertrophy with maximum wall thickness of 18.9±4 mm. Based on performed tests 34 patients (33.7%) were diagnosed with amyloidosis, including 17 cases of light-chain amyloidosis (AL), 16 of ATTR, and 1 case of other type of amyloidosis. Overall, patients with CA presented with mean 2.6±0.9 NYHA class. In TTE there was LV maximum wall thickness of 19.5±4 mm and LV mass value index value of 182±48 g/m 2, decreased global longitudinal strain value (GLS, −14.1±5%) and advanced diastolic dysfunction (EA 2.2±1.1, E/E' 22±9). Overall, there were 8 cases of ATTRwt and eight patients were diagnosed ATTRm. There were detected following types of TTR variants - c.302C>T p.(Ala101Val) in a single male patient, c.325G>A p.(Glu109Lys) in a single male patient and c.157T>C p.(Phe53Leu) in six patients. Overall, 10 patients with ATTR presented with polyneuropathy, additionally six had diagnosed carpal tunnel syndrome. All patients with ATTRm had positive family history for CA. Conclusions: In patients with unexpected LV hypertrophy evaluated in a cardiology referral center a high number of patients may suffer from underlying CA. Types of detected TTR gene variants associated with CA included most often Phe53Leu, and rare variants Ala101Val, Glu109Lys. FUNDunding Acknowledgement: Type of funding sources: None.